EVALUASI KAPASITAS SALURAN DRAINASE KECAMATAN TANETE RIATTANG TIMUR, KABUPATEN BONE - Kushari; Muhammad Taufik Iqbal, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
This research aims to determine the capacity of drainage channels based on input rainfall intensity and catchment area. The channel geometry properties were obtained from direct survey results in the field. EPA SWMM modeling was carried out to simulate drainage channel capacity. The drainage channel studied consists of 21 start/end points of the channel coded as JN. The number of channels reviewed was 29 channels with the code CN which are trapezoidal open channels with a total length of 28.92 km. Based on the results of EPA SWMM calculations and simulations, with a 5 year return period rainfall modeling scenario with an intensity of 24 hours, in general the channels still have the capacity to pass the designed discharge, there are only 4 channels that have inadequate capacity, namely CN4, CN5, CN16 and CN22. The necessary solution is to increase the cross-sectional area of the channel by dredging.